CATEGORY OF MODALITY IN LINGUISTICS - Juraeva Malohat Muhammadovna , (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
There are different viewpoints on the scientific-theoretical analysis of the category of modality. Specific feature of the application of this semantic category varies in different languages, as they differ in form and meaning. The reflection of modality in linguistics in due course changes, develops and becomes a reason of the emergence of new scientific and theoretical viewpoints.